BAHAYA LABELING NEGATIF TERHADAP PEMBENTUKAN KONSEP DIRI PADA ANAK TUNALARAS DENGAN TIPE GANGGUAN PERILAKU (CONDUCT DISORDER) DALAM PERSPEKTIF KONSELING LINTAS BUDAYA - Angga Yuda Meilanda (Universitas Borneo Tarakan, 2020)
Negative labeling is a form of negative stigma given by individuals or groups to other individuals or groups through a negative assessment of the deficiencies they have. Someone who is labeled will experience a change in role and tend to behave like the label given to him. One of them is tunalaras children who often get negative labels from people around because they experience obstacles in the development of emotional, social or both aspects, so that behavior tends to deviate, not in accordance with the age and demands of social norms prevailing in the environment. In this study, we will discuss the effects and dangers of negative labeling on children with disabilities with the type of conduct disorder on the formation of self-concept seen from a cross-cultural counseling perspective. If the problem is viewed through a cross-cultural perspective, negative labeling is an act that can cause social inequalities, for that children with conduct disorder really need cross-cultural counseling where cross-cultural counseling plays a role in helping the process of defining goals that are consistent with life experiences and values. the child's cultural values, recognizing the child's identity to include individual, group, and universal dimensions, supporting universal use and cultural specific strategies and roles in the healing process, and balancing the importance of individualism and collectivism in the assessment, diagnosis, and treatment of clients and client systems